2000
DOI: 10.1177/089033440001600211
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome: A Connection to Insufficient Milk Supply?

Abstract: Despite advances in lactation skills and knowledge, insufficient milk production still continues to mystify mothers and lactation consultants alike. Based on 3 cases with similar threads, a connection is proposed between polycystic ovary syndrome (PCOS) and insufficient milk supply. Described are the etiology and possible symptoms of PCOS such as amenorrhea/oligomenorrhea, hirsutism, obesity, infertility, persistent acne, ovarian cysts, elevated triglycerides, and adult-onset diabetes, along with possible path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Women with diabetes and those who give birth by Caesarean section may be more likely to experience delayed lactogenesis or low milk supply [60-62]. Some women with PCOS have insufficient milk supply, which is thought to be related to the endocrinological changes associated with the syndrome (high levels of androgens, insulin resistance, frequently low progesterone levels) [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Women with diabetes and those who give birth by Caesarean section may be more likely to experience delayed lactogenesis or low milk supply [60-62]. Some women with PCOS have insufficient milk supply, which is thought to be related to the endocrinological changes associated with the syndrome (high levels of androgens, insulin resistance, frequently low progesterone levels) [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common condition, and is associated with reduced fertility; however, most women with PCOS become pregnant and give birth 1,2 . Except for one case report and one pilot study, 3,4 little has been reported about PCOS and breastfeeding. For years, the clinical impression has been that fewer women with PCOS were breastfeeding, and in a small pilot study we found support for this observation 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the incidence of failure to lactate in the general population is 2–15% and has a multifactorial background . No woman in our cohort had risk factors, such as cosmetic breast surgery, treatment for breast malignancy and diagnosis of polycystic ovary syndrome …”
Section: Discussionmentioning
confidence: 71%